Application of the AERMOD modeling system for environmental impact assessment of NO_2 emissions from a cement complex - Seangkiatiyuth, Kanyanee; Surapipith, Vanisa; Tantrakarnapa, Kraichat; Lothongkum, Anchaleeporn W. (Journal of environmental sciences (China), 2011)
We applied the model of American Meteorological Society-Environmental Protection Agency Regulatory Model（AERMOD） as a tool for the analysis of nitrogen dioxide（NO2） emissions from a cement complex as a part of the environmental impact assessment.The dispersion of NO2 from four cement plants within the selected cement complex were investigated both by measurement and AERMOD simulation in dry and wet seasons.Simulated values of NO2 emissions were compared with those obtained during a 7-day continuous measurement campaign at 12 receptors.It was predicted that NO2 concentration peaks were found more within 1 to 5 km,where the measurement and simulation were in good agreement,than at the receptors 5 km further away from the reference point.The QuantileQuantile plots of NO2 concentrations in dry season were mostly fitted to the middle line compared to those in wet season.This can be attributed to high NO2 wet deposition.The results show that for both the measurement and the simulation using the AERMOD,NO2 concentrations do not exceed the NO2 concentration limit set by the National Ambient Air Quality Standards（NAAQS） of Thailand.This indicates that NO2 emissions from the cement complex have no significant impact on nearby communities.It can be concluded that the AERMOD can provide useful information to identify high pollution impact areas for the EIA guidelines.